2021
DOI: 10.3390/rs13132447
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variability of Chlorophyll-a and Sea Surface Temperature, and Their Relationship with Bathymetry over the Coasts of UAE

Abstract: The catastrophic implication of harmful algal bloom (HAB) events in the Arabian Gulf is a strong indication that the study of the spatiotemporal distribution of chlorophyll-a and its relationship with other variables is critical. This study analyzes the relationship between chlorophyll-a (Chl-a) and sea surface temperature (SST) and their trends in the Arabian Gulf and the Gulf of Oman along the United Arab Emirates coast. Additionally, the relationship between bathymetry and Chl-a and SST was examined. The MO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
0
4
0
2
Order By: Relevance
“…Produk konsentrasi klorofil-a aqua-MODIS Level 3 dihitung dengan algoritma MODIS OC3M (O'reilly et al, 1998). Algoritma OC3M merupakan fungsi polinomial yang menghubungkan reflektansi penginderaan jauh pada panjang gelombang 443, 488, dan 547 nm terhadap konsentrasi klorofil-a (Hussein et al, 2021).…”
Section: Sentinel-2 216unclassified
See 1 more Smart Citation
“…Produk konsentrasi klorofil-a aqua-MODIS Level 3 dihitung dengan algoritma MODIS OC3M (O'reilly et al, 1998). Algoritma OC3M merupakan fungsi polinomial yang menghubungkan reflektansi penginderaan jauh pada panjang gelombang 443, 488, dan 547 nm terhadap konsentrasi klorofil-a (Hussein et al, 2021).…”
Section: Sentinel-2 216unclassified
“…Produk konsentrasi 320 klorofil-a aqua-MODIS Level 3 dihitung dengan algoritma MODIS OC3M (O'reilly et al, 1998). 321 Algoritma OC3M merupakan fungsi polinomial yang menghubungkan reflektansi penginderaan jauh 322 pada panjang gelombang 443, 488, dan 547 nm terhadap konsentrasi klorofil-a (Hussein et al, 2021). 323 Spasio-temporal konsentrasi klorofil-a di wilayah perairan Tanjung Kelayang pada periode 324 perekaman tahun 2020 disajikan pada Gambar 7.…”
Section: Sentinel-2 216unclassified
“…Mohamed et al [12] also studied the change in SST in the Barents Sea using the EOF method, and concluded that the Barents Sea has the greatest changes in SST in the Arctic. Hussein et al [13] studied the correlations between chlorophyll-a and SST, and their trends in the Arabian Gulf. Zhao et al [14] analyzed the spatial and temporal characteristics of SST in the North Pacific Ocean and the correlations between SST and other sea factors.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the above-mentioned applications in ocean observation, this Special Issue presents various advanced ocean remote sensing technologies and their applications, including the use of artificial intelligence (AI) technology to explore ocean information [61][62][63][64] and reconstruct missing values [65,66]. The applications of ocean remote sensing detailed in this Special Issue include methods for the observation of changes in the ocean environment [67][68][69][70][71][72][73][74][75][76][77] and fishing ground [78], as well as the dynamics of the ocean, such as internal tides [79], internal waves [80,81], eddies and wakes [82,83], upwelling [84,85], ocean current [86][87][88][89] and even bibliometric analysis applied to oil detection and mapping [90]. A brief overview of the articles collected in this Special Issue is given below.…”
mentioning
confidence: 99%
“…The Chl-a and SST products from MODIS Aqua were used to study the events of harmful algae bloom (HAB) in the Arabian Gulf [71]. The results of the study show that the highest Chl-a concentration was in the Strait of Hormuz, with an average of 2.8 mg m −3 , which was 1.1 mg m −3 higher than the average of the entire study area.…”
mentioning
confidence: 99%